A Computational Modeling Study to Investigate the Use of Epicranial Electrodes to Deliver Interferential Stimulation to Subcortical Regions - Khatoun, Ahmad; Asamoah, Boateng; Mc Laughlin, Myles (Frontiers in Neuroscience, 2021)
Background: Epicranial cortical stimulation (ECS) is a minimally invasive neuromodulation technique that works by passing electric current between subcutaneous electrodes positioned on the skull. ECS causes a stronger and more focused electric field in the cortex compared to transcranial electric stimulation (TES) where the electrodes are placed on the scalp. However, it is unknown if ECS can target deeper regions where the electric fields become relatively weak and broad. Recently, interferential stimulation (IF) using scalp electrodes has been proposed as a novel technique to target subcortical regions. During IF, two high, but slightly different, frequencies are applied which sum to generate a low frequency field (i.e., 10 Hz) at a target subcortical region. We hypothesized that IF using ECS electrodes would cause stronger and more focused subcortical stimulation than that using TES electrodes. Objective: Use computational modeling to determine if interferential stimulation-epicranial cortical stimulation (IF-ECS) can target subcortical regions. Then, compare the focality and field strength of IF-ECS to that of interferential Stimulation-transcranial electric stimulation (IF-TES) in the same subcortical region. Methods: A human head computational model was developed with 19 TES and 19 ECS disk electrodes positioned on a 10–20 system. After tetrahedral mesh generation the model was imported to COMSOL where the electric field distribution was calculated for each electrode separately. Then in MATLAB, subcortical targets were defined and the optimal configurations were calculated for both the TES and ECS electrodes. Results: Interferential stimulation using ECS electrodes can deliver stronger and more focused electric fields to subcortical regions than IF using TES electrodes. Conclusion: Interferential stimulation combined with ECS is a promising approach for delivering subcortical stimulation without the need for a craniotomy.